2020
DOI: 10.3390/hydrology7030044
|View full text |Cite
|
Sign up to set email alerts
|

Flood Frequency Analyses over Different Basin Scales in the Blue Nile River Basin, Ethiopia

Abstract: The frequency and intensity of flood quantiles and its attendant damage in agricultural establishments have generated a lot of issues in Ethiopia. Moreover, precise estimates of flood quantiles are needed for efficient design of hydraulic structures; however, quantification of these quantiles in data-scarce regions has been a continuing challenge in hydrologic design. Flood frequency analysis is thus essential to reduce possible flood damage by investigating the most suitable flood prediction model. The annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Their analysis revealed that no single distribution can be considered ideal for Australia. To identify the best fit distribution, model selection, and goodness-of-fit tests such as the Akaike information criterion [88], Bayesian information criterion [89], Anderson-Darling test [90], Chi-squared test [91], Kolmogorov-Smirnov test [91], and probability plot correlation coefficient [92] have been used in previous studies [87,93]. Zhang et al [94] investigated the selection of a probability distribution for at-site FFA for Canadian basins and found that the GEV distribution is a suitable choice for most sites.…”
Section: • Importance Of Data Length In Ffa and Surrogatesmentioning
confidence: 99%
“…Their analysis revealed that no single distribution can be considered ideal for Australia. To identify the best fit distribution, model selection, and goodness-of-fit tests such as the Akaike information criterion [88], Bayesian information criterion [89], Anderson-Darling test [90], Chi-squared test [91], Kolmogorov-Smirnov test [91], and probability plot correlation coefficient [92] have been used in previous studies [87,93]. Zhang et al [94] investigated the selection of a probability distribution for at-site FFA for Canadian basins and found that the GEV distribution is a suitable choice for most sites.…”
Section: • Importance Of Data Length In Ffa and Surrogatesmentioning
confidence: 99%
“…Each extreme high flow simulation from each climate model simulation and bias corrected simulations were fitted to most dominant frequency models. Several researchers have been conducted flood frequency estimation, and they concluded that GEV and EV distribution models are the most commonly frequency models in Awash catchments (Tegegne et al 2020;Ahilan et al 2012). However, our numerical experiment result confirms that GEV distribution is the most dominant model type in the selected Awash catchments.…”
Section: Uncertainty In Flood Hazard Frequency and Magnitude And Deco...mentioning
confidence: 99%
“…Hassan et al [24] implemented the truncated power Lomax (TP-Lomax) distribution for analyzing the flood data set. For other studies related to the hydrology data sets, we refer to studies by Karahacane et al [25]; Dodangeh et al [26]; and Tegegne et al [27].…”
Section: Introductionmentioning
confidence: 99%